2012
DOI: 10.1108/20466851211279484
|View full text |Cite
|
Sign up to set email alerts
|

Teacher induction and mentorship policies: the pan‐Canadian overview

Abstract: Purpose -The purpose of this exploratory article is to address the questions of teacher attrition and retention by examining the policies supporting beginning teachers in different jurisdictions (provinces and territories) in Canada through teacher induction and mentorship programs. Design/methodology/approach -This research study relied on the collection of documents as the primary method of data collection. Both policy documents as means of external communication and the informal responses to formal policies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 62 publications
1
25
0
Order By: Relevance
“…The complexity of the mentoring process is exacerbated by the holistic nature of mentor roles (Clutterbuck, 2004). Mentors have professional development roles (as educators, as role models, as professionals who introduce the mentees to the culture of the school and facilitators helping mentees to gain access to resources) but also psychosocial support roles (as they have experienced what the mentees are experiencing and, therefore, know how to cope with it) (Garza et al, 2014;Hobson and Malderez, 2013;Kutsyuruba, 2012;Tan, 2012;Wyatt and Arnold, 2012). Dominguez and Hager (2013) and Parylo et al (2012), Tan (2013) noted that mentees prefer mentors who help them in their professional development.…”
Section: The Importance Of Mentor and Mentee In The Mentoring Processmentioning
confidence: 99%
See 2 more Smart Citations
“…The complexity of the mentoring process is exacerbated by the holistic nature of mentor roles (Clutterbuck, 2004). Mentors have professional development roles (as educators, as role models, as professionals who introduce the mentees to the culture of the school and facilitators helping mentees to gain access to resources) but also psychosocial support roles (as they have experienced what the mentees are experiencing and, therefore, know how to cope with it) (Garza et al, 2014;Hobson and Malderez, 2013;Kutsyuruba, 2012;Tan, 2012;Wyatt and Arnold, 2012). Dominguez and Hager (2013) and Parylo et al (2012), Tan (2013) noted that mentees prefer mentors who help them in their professional development.…”
Section: The Importance Of Mentor and Mentee In The Mentoring Processmentioning
confidence: 99%
“…Researchers studying mentoring relationships in the United States see mentoring as a form of "sponsorship", whilst researchers from the European tradition approach see mentoring as a means of supporting professional development (Brondyk and Searby, 2013, p. 193;Reddick, 2012, p. 37). Authors such as Kutsyuruba (2012) and Hobson and Malderez (2013), nonetheless incorporate both traditions by defining mentoring as a form of support and sponsorship towards professional development.…”
Section: Context and Cultural Influences On Mentoringmentioning
confidence: 99%
See 1 more Smart Citation
“…The effective support of teachers who are beginning their career remains a complex problem of practice in education. In Canada, researchers have estimated that as many as 40-50% of teachers leave in their first five years of the profession [1][2][3]. However, leaving is not the only detrimental outcome of challenging induction experiences.…”
Section: Introductionmentioning
confidence: 99%
“…Literature indicates mentoring fosters the professional development of student teachers, early career teachers, and experienced teachers (Aderibigbe, 2013;Aspfors & Bondas, 2013;Kutsyuruba, 2012). It is also reported that mentoring between teachers and student teachers underpinned by collaborative philosophy aids students' learning (Aderibigbe, 2013).…”
Section: Introductionmentioning
confidence: 99%